Novel fused arylpyrimidinone based allosteric modulators of the M1 muscarinic acetylcholine receptor - Mistry, Shailesh N.; Lim, Herman; Jörg, Manuela; Capuano, Ben; Christopoulos, Arthur; Lane, J. Robert; Scammells, Peter J. (ACS, 2016)
Benzoquinazolinone 1 is a positive allosteric modulator (PAM) of the M1 muscarinic acetylcholine receptor (mAChR), which is significantly more potent than the prototypical PAM, 1-(4-methoxybenzyl)-4-oxo-1,4-dihydroquinoline- 3-carboxylic acid  (BQCA). In this study, we explored the structural determinants that underlie the activity of 1 as a PAM of the M1 mAChR. We paid particular attention to the importance of the tricyclic scaffold of compound 1, for the activity of the molecule. Complete deletion of the peripheral fused benzene ring caused a significant decrease in affinity and binding cooperativity with acetylcholine (ACh). This loss of affinity was rescued with the addition of either one or two methyl groups in the 7- and/or 8-position of the quinazolin-4(3H)-one core. These results demonstrate that the tricyclic benzo[h]quinazolin-4(3H)-one core could be replaced with a quinazolin-4(3H)-one core and maintain functional affinity. As such, the quinazolin-4(3H)-one core represents a novel scaffold to further explore M1 mAChR PAMs with improved physicochemical properties.